Debris perturbed by radiation pressure: relative velocities across circular orbits - Celestino, C. C.; Winter, O. C.; Prado, AFBA (Elsevier B.V., 2004)
In the present work we consider a dynamical system of mum size particles around the Earth subject to the effects of radiation pressure. Our main goal is to study the evolution of its relative velocity with respect to the co-planar circular orbits that it crosses. The particles were initially in a circular geostationary orbit, and the particles size were in the range between 1 and 100 mum. The radiation pressure produces variations in its eccentricity, resulting in a change in its orbital velocity. The results indicated the maximum linear momentum and kinetic energy increases as the particle size increases. For a particle of 1 mum the kinetic energy is approximately 1.56 x 10(-7) J and the momentum is 6.27 x 10(-11) kg m/s and for 100 mum the energy is approximately 1.82 x 10(-4) J and the momentum is 2.14 x 10(-6) kg m/s. (C) 2004 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: space debris; radiation pressure; geostationary orbit